The french abysm the chilean conservative and the revolutionary france 1964-1890 (2011)
This text aims at building a sight that the Chilean Conservative of the second half of XIX century had upon revolutionary tradition in France. Since the study of the parliamentary speeches and the politics works of conjuncture elaborated by the conservative between 1864 and 1890 as well as the inquest of the magazine “The independent”, members of the conservative party argued courageously with the radical and liberal press house of Chile. It is shown that a conservative mentality in Chile explained the breaking of the current time, secularization of the public life and the spoil of the temporary powers of the Catholic Church since the “pernicious” inluence of the “fatal doctrines” coming from the “Evil France” that had in the reddish the “Liberalism of the bad law” and the “Jacobean Liberalism to its main proponents.